The Lost Child - Stefanova Radoulska, Svetlana (Wasafiri, 2017)
The Lost Child is composed of several fragmented storylines focused on Monica and her two children’s struggle to survive economic hardship and endure isolation, prejudice and loneliness. The narrative shifts in time and perspective, producing a multiplicity of dimensions and layers. It displays a sophisticated web of allusions not only to the canonical text, but also to themes, motifs and characters which Phillips explores in his previous works, enriching them with fresh insights.
Keywords: reseña; libros; WOS